PENGARUH OPERATING PROFIT MARGIN, DIVIDEND PAYOUT RATIO, PROFITABILITAS, DAN PRICE EARNING RATIO TERHADAP PRAKTIK PERATAAN LABA PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Rulfah M Daud (Jurnal Akuntansi Muhammadiyah (JAM), 2017)
The objectives of this research are to examine (1) the effect of operating profit margin, dividend payout ratio, profitability, and price earning ratio simultaneously on income smoothing, and (2) the effect of operating profit margin, dividend payout ratio, profitability, and price earning ratio partially on income smoothing.            The method used in this research is purposive sampling method. The sample of this research is LQ-45 company listed in Indonesia Stock Exchange during 2010 until 2014. The analysis method used in the research is logistic regression.            The result of this research are (1) operating profit margin, dividend payout ratio, profitability, and price earning ratio simultaneously have an effect on the income smoothing, (2) operating profit margin and dividend payout ratio partially have an affect the income smoothing and, (3) profitability and price earning ratio have not effect on the income smoothing